Pink1/Parkin signaling mediates pineal mitochondrial autophagy dysfunction and its biological role in a comorbid rat model of depression and insomnia - Zirong Li; Yi Shu; Deguo Liu; Sheng Xie; Liangbo Xian; Jiaqi Luo; Xiuwen Huang; Haixing Jiang (Brain Research Bulletin)
Using a chronic unpredictable mild stress (CUMS) combined with multi-platform water environment sleep deprivation (SD) as an animal model, the occurrence and development of human depression combined with insomnia were simulated. The abnormal mitochondrial autophagy signaling caused by the putative kinase 1/Parkin E3 ubiquitin protein ligase (Pink1/Parkin) signaling pathway directly affects the normal secretion of melatonin by the pineal gland, which may explain the pathogenesis of depression combined with insomnia. This study aims to explore the depression-like behavior, sleep changes, central oxidative stress response, pineal mitochondrial autophagy damage, melatonin secretion, histopathological changes of the pineal gland, and the expression of Pink1/Parkin signaling-related factors in CUMS+SD rats. The results showed that the levels of reactive oxygen species (ROS) in cerebrospinal fluid of CUMS+SD rats significantly increased along with the inflammatory factors Interleukin-1β (IL-1β) and nuclear factor kappa-B (NF-κB) in cerebrospinal fluid. In addition, the number of pineal gland cells significantly decreased, cell boundaries became blurred, cell volume shrank, and apoptotic bodies appeared in the pineal gland tissue under HE staining, indicating pineal gland inflammation. Sleep deprivation further disrupted the levels of autophagy damage factors, including histamine (MDA), glutathione (GSH), and catalase (CAT), in the cerebrospinal fluid of CUMS+ SD rats. Transmission electron microscopy of the pineal gland in CUMS+SD rats revealed damage to mitochondrial autophagy. The levels of 5-hydroxytryptamine (5-HT) and aromatic amine-N-acetyltransferase (AANAT) in the cerebrospinal fluid, as well as melatonin levels in the pineal gland, were significantly decreased. Additionally, the expression of IL-1β, NF-κB, Pink1, and Parkin in the pineal gland of CUMS+SD rats significantly increased. The expression of microtubule-associated protein 1 light chain 3-β (LC3), selective autophagy adaptor protein (P62), cytochrome c oxidase IV (COXIV), and mitochondrial outer membrane translocation enzyme 20 (TOM20) proteins downstream of the Pink1/Parkin signaling pathway was enhanced, while the expression of downstream brain-derived neurotrophic factor (BDNF), Beclin 1, and BCL2 interacting protein 3 (BNIP3) proteins was negatively regulated. Pink1/Parkin signaling may specifically respond to mitochondrial autophagy damage in the pineal gland, affecting the normal synthesis and secretion of melatonin in the pineal gland. In summary, mitochondrial autophagy damage in the pineal gland affects the normal secretion of melatonin in CUMS+SD rats, which is closely related to the specific autophagy signaling impairment of Pink1/Parkin pathway, which may mediate the occurrence of depression combined with insomnia.